2019
DOI: 10.1101/699983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing rigor and reproducibility in maternal immune activation models: practical considerations and predicting resilience and susceptibility using baseline immune responsiveness before pregnancy

Abstract: Despite the potential of rodent models of maternal immune activation (MIA) to identify new biomarkers and therapeutic interventions for a range of psychiatric disorders, their value is currently limited by issues of scientific rigor and reproducibility. Here, we report three sources of variability-the immunogenicity of the poly(I:C), the baseline immune responsiveness (BIR) of the females prior to pregnancy, and differences in immune responses in C57/B6 dams across vendors. Similar to the variable effects of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…C57BL/6N females (Charles River, Kingston, NY), were bred in house and maintained on a 12:12 hr light dark cycle at 20 ± 1°C, food and water available ad libitum. Mice utilized in this study do harbor Segmented Filamentous Bacteria (SFB) ( Estes et al, 2019 ). Males and females embryos were analyzed across experiments, sex was determined as previously described ( McFarlane et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6N females (Charles River, Kingston, NY), were bred in house and maintained on a 12:12 hr light dark cycle at 20 ± 1°C, food and water available ad libitum. Mice utilized in this study do harbor Segmented Filamentous Bacteria (SFB) ( Estes et al, 2019 ). Males and females embryos were analyzed across experiments, sex was determined as previously described ( McFarlane et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…), timing of immunogen administration, dosage, route of administration, housing conditions, timing of cage cages and mouse strain used (Careaga et al, 2018;Kentner et al, 2019;Kowash et al, 2019), understanding what causes these differences could aid in understanding the mechanisms underlying vulnerability versus resiliency to MIA (Meyer, 2019). In humans, only a subset of pregnant mothers who are exposed to a viral or bacterial infection have offspring who later develop SCZ (Estes et al, 2019). This is to be expected since immune activation is only one of the many risk factors for SCZ.…”
Section: Mia Enhances Risk For Scz By Altering Microglial Functionmentioning
confidence: 99%
“…In numerous studies, pup weight is shown to be smaller in poly The results in this chapter were generated to validate and improve understanding of the natural variation in this model, according to recent recommendations and reviews [125,178]. While this evidence does not support maternal weight and pup weight alterations, it does show a fever-driven temperature change in poly I:C group dams.…”
Section: Pup Weightsmentioning
confidence: 98%
“…Unvalidated and unequal immune responses are estimated to be one of the biggest sources of variation and conflict between MIA studies [125,179]. For example, variable molecular weights in commercial batches of poly I:C have been shown to elicit different strengths of immune response [178,180]. Without reporting poly I:C weight or quantifying immune response, studies that appear to use comparable models may not be.…”
Section: Maternal Immune Responsementioning
confidence: 99%